Eyelid molluscum contagiosum presenting as a giant solitary ulcerating mass - Alrajeh, Mohammed (Saudi J Ophthalmol, 2018)
Molluscum contagiosum is a benign viral cutaneous infection. It typically presents as an asymptomatic centrally umbilicated nodule 3–5 mm in diameter. Susceptible patients are children and adults receiving immunosuppressive therapy. We report a case of an eyelid molluscum contagiosum in a 5-year-old boy with no risk factors and a 2-week history of a large localized ulcerating mass of the left upper eyelid. The mass was totally excised, and diagnosis of molluscum contagiosum was confirmed in the histopathology study. Microscopic examination revealed enlarged keratinocytes, and acquired eosinophilic Henderson-Patterson inclusion bodies were also detected. Such ulcerating solitary lesions can be misdiagnosed as infected epidermal cysts, keratoacanthoma, or infected chalazions; therefore, molluscum contagiosum should be considered in the differential diagnosis. Complete excisional biopsy of the mass is diagnostic and curative.